Toward a New Instrumental Macroeconomics: Abba Lerner and Adolph Lowe on Economic Method, Theory, History, and Policy - Mathew Forstater (Levy Economics Institute of Bard College, 1998)
This paper argues that the ideas of Abba Lerner and Adolph Lowe contain overlapping and complementary insights and themes that may contribute to the development of a new approach to macroeconomics and that have rather specific practical policy implications. Lerner's notions of functional finance and money as a creature of the state are combined with Lowe's structural analysis to forge an approach to macroeconomic theory and policy that considers both aggregate proportionality and balance and sectoral relations and that addresses issues regarding monetary production and effective demand as well as ongoing structural and technological change. Such a "new instrumental macroeconomics," focusing on full employment, price stability, and a decent standard of living for all, has important points of contact with recent proposals promoting job opportunities through direct job creation with a public service corps that benefits communities while serving as a buffer stock of labor providing price stability.
Keywords: 330